Embracing the sustainable performance of Nigeria's small and medium enterprises: understanding and promoting the self leadership development of the owners - Nnaemeka Enem, Godwin; Mohd Anuar, Mohd Ashraff; Abdul Wahat, Nor Wahiza; Ismail, Ismi Arif (Human Resource Management Academic Research Society, 2023)
The governments and owners of small and medium enterprises (SMEs) must proactively work towards embracing sustainable performance among SMEs, given their pivotal economic roles in nations worldwide. From the perspective of SME owners, self-leadership emerges as a potent tool, enabling them to guide themselves effectively by acquiring specific behavioral and cognitive skills, thereby enhancing both their personal lives and entrepreneurial operations. Despite the wealth of literature available on entrepreneurship and self-leadership, the discourse on self-leadership among entrepreneurs remains limited and in its early stages. This qualitative study aims to provide a comprehensive understanding of self-leadership development among ten seasoned SME owners, each with over a decade of experience in both business management and ownership in Nigeria. Participants were meticulously chosen and interviewed using purposive and snowball sampling techniques. The qualitative data were managed using Nvivo 11 Pro, and thematic analysis was employed as the analytical approach. The study's findings illuminate five crucial pathways through which these experienced owners cultivated their self-leadership skills. These pathways, applicable to new SME owners, include: (i) continuous learning; (ii) spirituality; (iii) persistence in managing environmental uncertainty; (iv) engagement in apprenticeship programs; and (v) willingness to take risks and exhibit proactive behavior. This paper contends that understanding the self-leadership development of these seasoned SME owners not only strengthens their individual capacities but also serves as a valuable reference for promoting self-leadership among emerging SME owners, thereby influencing the long-term performance of their businesses.